Impact of tourism, globalization, and technological patents on ecological footprint in ASEAN countries: static and dynamic panel regression approaches - Nazhat Nury Aspy; Liton Chandra Voumik; Miguel Angel Esquivias; Lilik Sugiharti; Mihir Kumar Das; Dulal Chandra Pattak (Discover Sustainability)
Abstract This study aims to investigate the intricate relationship between multiple socioeconomic, human capital, and technological factors and their impacts on the ecological footprint within the ASEAN region. Focusing on eight ASEAN nations (Brunei, Cambodia, Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam) for the period between 1990 and 2020, this study employs Driscoll Kraay Standard Error (DKSE) and Quantile Regression methodologies to examine this phenomenon comprehensively. The findings reveal that the Human Capital Index (HCI) and technological patents exhibit negative coefficients, suggesting their beneficial impact on reducing ecological footprint by 0.162% and 0.027% sequentially in the DKSE approach. By contrast, population, GDP, tourism, globalization, and trade openness show positive coefficients, indicating their potential to exacerbate environmental degradation. Notably, population emerged as the most detrimental factor. Meanwhile, HCI demonstrated the most potent beneficial effect on environmental quality, suggesting that ASEAN nations should continue investing in their people to safeguard the environment. The implications of this study are critical for policymakers and stakeholders in the ASEAN region, highlighting the need for strategic interventions that balance economic and technological advancements with environmental preservation.